Pharmacological Activities of Graviola (Annona muricata): A Mini-Review - Salem, Areej I.; Abd El-Fadil, Hosny; Al-Sayed, Nagaah; Alazzouni, Ahmed S.; El-Nabtity, Sameh (Journal of Advanced Veterinary Research, 2022)
Graviola (Annona muricata) is one major member of the plant family, Annonaceae. It is cultivated in the tropical zones, particularly in Central and South America. Graviola is worldwide known for its natural medicinal effects. In this regards, graviola extracts are used in the treatment of different kinds of cancers such as pancreatic, breast, prostate, lung, and blood cancers. The exact mechanisms behinds the anticancer effects of graviola are not clearly defined. However, it was assumed that graviola-induced apoptotic effects, necrosis, and modulation of the proliferation patterns of the cancer cells are major mechanistic effects of Graviola. Interestingly, graviola is also known for its other beneficial effects such as its antioxidant, anti-inflammatory, anti-rheumatic activities, and its wound healing effects. This mini review was undertaken to update and summarize the pharmacological activities of graviola.